International Health Regulations and international human mobility: An analysis of the Brazilian case during the Covid-19 pandemic - Borges, Daniel Damásio [UNESP]; Rodrigues, Maria Eduarda [UNESP]; Ribeiro, Flávia Oliveira [UNESP] (Revista Brasileira de Estudos Politicos, 2023)
During the Covid-19 pandemic, states employed restrictive health measures that affected rights, such as freedom of movement, impacting international human mobility, with practices such as closing borders. Such tendency to portray health emergencies as a national security agenda rather than a public health agenda, in a process of health securitization, opposes the idea of Global Health Security, promoted by WHO, in its main body, the International Health Regulations (IHR), whose general orientation is firmly against the imposition of border restrictions, and remained so during the Covid-19 pandemic. The objective of the present study is to analyze the measures imposed by the Brazilian government on international mobility during this health emergency. Therefore, in the methodological field, we employed the deductive approach method and the bibliographic research technique. The analyses begin with a review of the literature on the subject and the contexts of scientific production. From this analysis it was possible to conclude that the Brazilian restrictive measures to international human mobility occurred in an uncoordinated way, without the elaboration of a health security protocol for the different types of Brazilian borders, which enabled the use of discriminatory practices, in disagreement with the IHR and the protection of human rights.
Regulamento Sanitário Internacional e mobilidade humana internacional: uma análise do caso brasileiro durante a pandemia da Covid-19
Keywords: Covid-19; Direitos Humanos; Emergência sanitária; Human rights; International Health Regulations; International Human Mobility; Mobilidade Humana Internacional; Regulamento Sanitário Internacional; Sanitary emergency